Developing and Adapting a Family-based Diabetes Program at the U.S.-Mexico Border - Nicolette I. Teufel-Shone, PhD; Rebecca Drummond, MA; Ulrike Rawiel, MS (Centers for Disease Control and Prevention, 2005)
Context The prevalence of diabetes among Hispanics is more than twice that of non-Hispanic whites in communities along the U.S.-Mexico border. The University of Arizona and two community health agencies on the Arizona border, Campesinos Sin Fronteras and Mariposa Community Health Center, collaborated to design, pilot and assess the feasibility of a lay health-outreach worker- (promotora-) delivered diabetes education program for families. La Diabetes y La Unión Familiar was developed to build family support for patients with diabetes and to teach primary prevention behaviors to family members. Method Community and university partners designed a culturally appropriate program addressing family food choices and physical activity, behavior change, communication, and support behaviors. The program offers educational content and activities that can be presented in home visits or multifamily group sessions. Community partners led the implementation, and university partners guided the evaluation. Consequences Seventy-two families (249 total participants) including children and grandchildren participated. Preintervention and postintervention questionnaires completed by adults (n = 116) indicate a significant increase in knowledge of eight diabetes risk factors (P values for eight factors range from <.001 to .006) and a significant increase in family efficacy to change food (P < .001) and activity behaviors (P < .001). Interviews with participants highlight the programs positive psychosocial impact. Interpretation Community and university collaboration involved building upon the promotoras' expertise in engaging the community and the universitys expertise in program design and evaluation. A promotora-delivered family-based diabetes prevention program that emphasizes family support, communication, and health behaviors is feasible and can yield change in family knowledge, attitude, and behavior relative to diabetes risk factors.